Penguatan Strategi Pemasaran Digital Pada UMKM Wisata Kuliner di Kota Tomohon - Wuisan, Yesita Windi; Hullah, Abdurrahman Rigel; Butarbutar, Tarida Elisa (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The development of technology that is inevitable due to a shift in people's behavior and tastes that used to be traditional conventional shopping is now changing more using digital marketing platforms. The use of digital technology-based marketing concepts is a hope for MSMEs to develop into centers of economic power. Digital marketing promotion media is expected to be an effective choice for MSME actors in developing their business and reaching national and international markets. The method in this study is qualitative research where data is collected through in-depth interviews with MSME owners who have implemented digital marketing strategies. The purpose of this research is to help Culinary MSME business actors in the city of Tomohon use social media as a means for them to promote and also provide an understanding of the importance of digital marketing in introducing their products widely.